Legal Protection For Workers Who Have Been Terminated For Absenteeism - Wahyuningsih, Virliana (Universitas Islam kadiri, 2025)
It is well-known among the public that Indonesia is a country where development in various sectors, especially in the economy, is consistently successful and supported by the government. One of the most prominent sectors is the industrial sector, which is significantly encouraged by the government. This is the aim of this research: first, to explore the legal protection provided for workers whose employment is terminated due to absenteeism. Second, to investigate the legal recourse available if a worker's employment is terminated due to absenteeism. In this research, the author employs a Normative Legal Research Method. In this study, the author contends that the judge correctly interpreted Article 27 paragraph (9) letter e and Article 27 paragraph (10) of the Collective Labor Agreement (CLA) of PTFI (PT Freeport Indonesia) for the periods of 2015-2017, as well as Article 26 paragraph (10) of the CLA of PTFI for the periods of 2017-2019, and Article 168 paragraph (1) of Law Number 13 of 2003 concerning Manpower, along with relevant prevailing laws. Consequently, the decision was accepted, resulting in the termination of the employment relationship between PT Freeport Indonesia and Ferdinandt Mamangkey upon the enforcement of this decision.Keywords: Legal Protection, Absenteeism, Termination, Judge